Gatunek pamięci zbiorowej. Rekonesans - Marta Wójcicka (Stylistyka, 2019)
Collective memory, defined as ‘acollection of imagesof community members about their past which are included in cultural texts,’ (Wójcicka 2015: 68), ‘images about the past activated in the process of social communication in order to meet the cul-tural and political needs of the present’ (Czachur 2018: 11), is unavailable directly. It can be reached only through representation of the past expressed in different kinds of signs. Thus, collective memory has the character of a sign. Based on that assumption, the author presents the style and genre diversity of collective memory. She shows the role of language style in collective memory and puts forward a ques-tion about what function speech genre has in remembering, recalling, reminding and forgetting. She presents complex relations between memory and speech genre, which she treats as a sign of oblivion. In the last part of the article, the author offers a typology of memory genres distinguishing primarily (intentionally) mnemonic and secondarily(functionally) mnemonic genres.